Prognostication in Anoxic Brain Injury. (November 2018) - Nguyen, Kim Phung L.; Pai, Vandana; Rashid, Saima; Treece, Jennifer; Moulton, Marie; Baumrucker, Steven J.
Cardiac arrest is a common cause of coma with frequent poor outcomes. Palliative medicine teams are often called upon to discuss the scope of treatment and future care in cases of anoxic brain injury. Understanding prognostic tools in this setting would help medical teams communicate more effectively with patients' families and caregivers and may promote improved quality of life overall. This article reviews multiple tools that are useful in determining outcomes in the setting of postarrest anoxic brain injury.